KONFIGURASI INTER VIRTUAL LOCAL AREA NETWORK MENGGUNAKAN ROUTING PROTOCOL OPEN SHORT PATH FIRST DENGAN SIMULASI PACKET TRACER - Suyanto Suyanto; Melisa Risanjani (Jurnal informasi dan komputer, 2017)
ABSTRAKThe utilization of computer network technology as a medium of communication of data is currently increasing. The need for the use of shared resources that exist in both hardware and software network has resulted in the incidence of various technological development network itself. Along with the increasing level of needs and the growing number of network users who want a form a network that cal deliver maximum results both in terms of efficiency as well as an increase in the security of the network itself.The task of the end of this writer did a variety of research. The stage of this research, looking for gather what is required to the configuration of Inter Virtual Local Area Network using OSPF routing. In addition to the research stage of the write also do a method of drafting the system, the method used is a method of PPDIOO. PPDIOO is the methodology developed by cisco system (cisco, 2005)Based on the desire, consummation hence efforts continue to be done by various parties. By utilizing a variety of techniques subnetting particularly, configuration, the use of routing OSPF and use of hardware better, another switches between the emergence of the concept of an area of Inter Virtual Network (Inter VLAN) that is expected to provide tissue that broader, large and better results than Local Area Network (LAN)